Ambiguous transitions : gender, the state, and everyday life in socialist and postsocialist Romania - Massino, Jill (Berghahn Books, 2019)
Focusing on youth, family, work, and consumption,'Ambiguous Transitions analyzes the interplay between gender and citizenship postwar Romania. By juxtaposing official sources with oral histories and socialist policies with everyday practices, Jill Massino illuminates the'gendered dimensions of socialist modernization and its complex effects'on women's roles,'relationships, and identities.'Analyzing women as subjects and agents, the book examines how they negotiated the challenges that arose as Romanian society modernized, even as it clung to traditional ideas about gender. Massino concludes by exploring the ambiguities of postsocialism, highlighting how the legacies of the past have shaped politics and women's lived experiences since 1989.